Revision as of 13:41, 12 September 2008 by Johns311 (Talk)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Going through the system first and then the time shift:

x[n] -> y[n] = (k + 1)^2x[n-(k+1)]

y[n] -> z[n] = y[n-1]

 = (k+1)^2x[n-1-(k+1)]


Going through the time shift first and then the system:

x[n] -> y[n] = x[n-1]

y[n] -> z[n] = (k+1)^2y[n-(k+1)]

 = (k+1)^2x[n-1-(k+1)]

Since the two results are the same, the system is time invariant.

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett